Uporaba geografskega informacijskega sistema pri načrtovanju prostorskega razvoja na primeru katastrskih občin Godovič in Črni Vrh - Kobler, Andrej (Geografski vestnik, 2000)
A case of the geographic information system supported planning for urban settlement, industry and tourism in the Godovič and Črni Vrh cadastral municipalities is presented in the paper. Three long term forecast of possible development scenarios were defined: population decline, moderate and fast population growth. Necessary areas for each land use and each scenario based on standards and normatives were determined and then allocated into the environment. This allocation was performed using the Eastman method, emphasising holistic approach and taking multiple criteria into consideration. First the suitability maps were produced and then multiple criteria were combined into a synthetic land use map.
Keywords: prostorski informacijski sistemi; geografski informacijski sistemi; prostorsko planiranje; spatial planning; regionalni razvoj; prostorski razvoj; Godovič; Črni Vrh